New sources of scholarly information - Codina, Lluís (Anuario ThinkEPI, 2010)
The basic characteristics of use and consumption of scientific, technical and medical (STM) information are described, and three newly created information resources are presented: DeepDyve; Science Research from Deep Web Technologies; and WorldCat, from OCLC. Also mentioned are the services Q-Sensei, Base, Scitopia and Lumifi.